2018
DOI: 10.1002/joc.5723
|View full text |Cite
|
Sign up to set email alerts
|

Late spring soil moisture variation over the Tibetan Plateau and its influences on the plateau summer monsoon

Abstract: Based on the European Centre for Medium-Range Weather Forecasts (ECMWF) ERA-Interim reanalysis data from 1979 to 2016, an index for Tibetan Plateau (TP) soil moisture (I TPSM ), which could represent inter-annual variation in spring soil moisture, is defined after removing the linear trend in soil moisture. The late spring soil moisture variation over the TP and its influences on the plateau summer monsoon are analysed. The results show that the TP soil moisture variation is non-uniform, and spring soil moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…The proposed mechanism may be attributed to multiple processes and may not only depend on soil moisture; however, further studies with model experiments will better delineate the underlying mechanism. In a previous study, similar local feedback between soil moisture precipitation is reported with a strong correlation between eastern plateau spring soil moisture and TP monsoon precipitation involving a similar mechanism observed in the current study (Zhou et al 2018).…”
Section: Summary and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The proposed mechanism may be attributed to multiple processes and may not only depend on soil moisture; however, further studies with model experiments will better delineate the underlying mechanism. In a previous study, similar local feedback between soil moisture precipitation is reported with a strong correlation between eastern plateau spring soil moisture and TP monsoon precipitation involving a similar mechanism observed in the current study (Zhou et al 2018).…”
Section: Summary and Discussionsupporting
confidence: 91%
“…The latent heat of condensation over eastern TP enhances the diabatic heating and leads to strong vertical ascending motion (Anmin et al 2012;Zhang et al 2016;Zhou et al 2018). In spring, TP's energy pro le can be largely attributed to soil moisture anomalies; thus, the energy released may also be subjected to soil moisture, which resulted from winter snow cover and springtime precipitation.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The East Asian summer monsoon (EASM) is significantly related to the land‐ocean temperature gradients between the continental East Asia and neighbouring oceans (Zhang et al ., 2013; Liu et al ., 2017). The temperature gradients prior to the onset of monsoons can be modulated by warming or cooling of the continental East Asia, which is related to the pre‐monsoonal soil moisture variability via surface energy budget (Koster and Suarez, 2001; Douville, 2002; Alexander, 2011; Dirmeyer, 2011; Asharaf et al ., 2012; Li et al ., 2015; Berg et al ., 2017; Varikoden and Revadekar, 2018; Wang et al ., 2018; Zhong et al ., 2018; Zhou et al ., 2018). Using observational analyses and numerical simulations, previous studies suggested that wet soil in spring over the vast region from the lower and middle reaches of the Yangtze River valley to North China (YRNC) corresponds to a cooling land surface in May, resulting in a reduced land‐sea thermal contrast and thereby a weakened EASM (Zhang and Zuo, 2011; Zuo and Zhang, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The response of soil organisms to short-term favorable conditions, following thawing and snowmelt, was immediate and short-lived [109], and the annual mean values of precipitation and temperature were not as representative as we expected. Second, Zhou et al [123] found that the variation in soil moisture on the Tibetan Plateau was non-uniform, and that geographic position and the summer monsoon, together, affected the relationship between precipitation and soil moisture. The heterogeneity of this relationship made the correlation between soil nematodes and climatic factors no longer general at the large scale.…”
Section: Roles Of Biotic and Abiotic Factors In Relation To The Nematode Communitymentioning
confidence: 99%